Impact of the COVID-19 Pandemic on Burnout in Primary Care Physicians in Catalonia - Seda-Gombau, Gemma; Montero-Alía, Juan José; Moreno-Gabriel, Eduard; Torán-Monserrat, Pere (International journal of environmental research and public health, 2021)
Background: Recent demands to raise the clinical quality, improve the patient experience, and decrease costs have progressively increased burnout among primary care physicians. This overstretched situation has been greatly aggravated since the onset of the COVID-19 pandemic. The aim of the study is to analyse the prevalence of burnout among primary care physicians and to assess the impact of the COVID-19 pandemic on burnout. Methods: This was a multicentre longitudinal descriptive study of occupational factors and burnout before and since the start of the COVID-19 pandemic. In order to assess the impact of the pandemic on burnout in primary care physicians, two paired groups of physicians were compared using Wilcoxon’s and McNemar’s tests. Results: In January 2019, 10% of primary care physicians scored high on all burnout domains. Seven months into the COVID-19 pandemic (October 2020), this percentage increased to 50%. Paired groups analysis showed unprecedented worsening due to the pandemic: emotional exhaustion, which already affected 55% of primary care physicians, jumped to 77%. Conclusions: Burnout is endemic among primary care physicians. It has been associated with lower patient satisfaction, reduced health outcomes, and increased costs. The COVID-19 pandemic has pushed burnout in primary care professionals to the edge.